Mechanical Behaviors of Epoxy Resins with Phenolic Formaldehyde Resin Reinforced by Nanoparticles - Ziad T. Khodair (Journal of Global Pharma Technology, 2016)
The importance of Nano molecular polymers has grown in the industry, depending on its mechanical and physical properties. With the development and growth of technology, engineering applications of polymers have increased, combining light weight and high density, enabling them to be used in high performance applications. The present research aims to study the mechanical behavior of epoxy resin with phenol formaldehyde resin and the reinforcement of Graphite nanoparticles (10 nm) and weight loss (0-40%). These characteristics include compressive force, flexural force, and elastic coefficient. The results showed an improvement in the properties of composite materials after reinforcement by graphite (Nano and micro), which will increase the properties by increasing the proportion of nanoparticles compared to micro particles.